2020
DOI: 10.33549/physiolres.934133
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of Propofol on High-Dose Remifentanil-Induced Hyperalgesia

Abstract: We aimed to evaluate the regulatory effects of propofol on high-dose remifentanil-induced hyperalgesia. A total of 180 patients receiving laparoscopic cholecystectomy were randomly divided into sevoflurane + high-dose remifentanil (SH) group, sevoflurane + low-dose remifentanil (SL) group and propofol + high-dose remifentanil group (PH) group (n=60). After intravenous administration of midazolam, SH and SL groups were induced with sevoflurane and remifentanil, and PH group was induced with propofol and remifen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This is supported by several studies demonstrating attenuation of OIH/AOT when remifentanil is used in the context of propofol as opposed to volatile agents. [33][34][35] The antagonism of NMDA by propofol may also render further NMDA antagonism by ketamine superfluous, explaining the absence of significant effect ketamine use or dosage on MEQ72 in our multivariable regression analysis. Several other groups, including a study from our centre examining AIS patients, have similarly shown no effect of ketamine on ameliorating OIH/AOT in the context of a propofol anesthetic.…”
Section: Anesthesia and Analgesiamentioning
confidence: 93%
“…This is supported by several studies demonstrating attenuation of OIH/AOT when remifentanil is used in the context of propofol as opposed to volatile agents. [33][34][35] The antagonism of NMDA by propofol may also render further NMDA antagonism by ketamine superfluous, explaining the absence of significant effect ketamine use or dosage on MEQ72 in our multivariable regression analysis. Several other groups, including a study from our centre examining AIS patients, have similarly shown no effect of ketamine on ameliorating OIH/AOT in the context of a propofol anesthetic.…”
Section: Anesthesia and Analgesiamentioning
confidence: 93%
“…As the most e ective type of minimally invasive surgery for the treatment of gallbladder disease, it excels owing to its small incision, less bleeding, fast recovery time, and high clinical e cacy [1]. Clinical studies have pointed out that in the treatment of laparoscopic cholecystectomy, treatment e ects using di erent anesthesia methods are varying [2,3]. Previously, clinical anesthesia for patients undergoing laparoscopic cholecystectomy majorly used fentanyl plus propofol, but the anesthesia e ect yet remains unsatisfactory [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in these conditions, clinicians need to be cautious about the possible occurrence of acute opioid tolerance 24,25,48 and OIH, which may impair pain treatment or even worsen pre-existing pain. According to the previously reported results, coadministration of anaesthetic drugs, such as propofol, 43,45 nitrous oxide, 49 magnesium, 42 ketamine, 5,39 and dexmedetomidine, 50 seem to be helpful to modulate the development of OIH, even if their modulatory effect needs to be further explored. However, there is a lack of validated approaches to diagnose OIH, which may limit the relevance of these results.…”
Section: Discussionmentioning
confidence: 99%